Sun Tzu’s Dao of Deceit Considering from a Semiotic Perspective - Xu, Jieping; Hemchua, Saengchan (Technium Social Sciences Journal, 2022)
Semioticians’ efforts on lie study, mostly focus on lie and sign relationship, its general characteristics on the basis of a static analysis. Sun Tzu’s The Art of War, the existing oldest treatise with the theme on lie whose influence extends beyond battle to other competitive spheres such as politics and business by modern readers cannot be overlooked. Sun Tzu, in contrast to semiotic studies of lying, focuses on the dynamic process of lie-sign signification, stating that lie formation is preconditioned by sign observation from the sender, the recipient, and the surrounding environment. He proposes his Xing (形) theory that the manipulation of recipient through the use of signs is the key to subdue him; he presents the formulating process of a lie-sign from the standpoint of a deceiver, which is uncommon in western culture. This study can shed new light on both the classic and the process of L-sign formulation and signification.